Bali Krisis Kesehatan Mental : Sebuah Kajian Literatur - agestin, lilik; Aristuti , Mega Puspa; Kartika, Diah Shinta (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2025)
The problem of suicide cases is one of the things that deserves attention in Indonesia, especially the province of Bali. It was recorded that in 2023 Bali became one of the provinces that occupied the first level from the average of all provinces in Indonesia. The phenomenon of mental health problems, namely suicidal behavior, causes something negative and harms oneself, causing death. This study aims to determine how the focus of the psychological dynamics of suicidal behavior is using the literature review method. The purpose of this review is to report the results of research that focuses on the psychological dynamics of suicidal behavior. The search for articles in this study used a search for journal articles published in 2019-2024 with the Google Scholar database with the criteria for the keywords psychological dynamics and suicidal behavior. The results of this study show the psychological dynamics of a person that causes suicidal behavior, namely experiencing severe stress, discomfort, depression and psychological trauma. This condition of course has an effect so that individuals are unable to deal with pressure, so that they can harm themselves. If that feeling arises, then a person tends not to think